Analysis Of Profit Of Sagu Business On Industries Business In Household Industries In East Kolaka Regency (Case Study On Bagea Sukses Bersama): Case Study on Bagea Sukses Bersama - Natasya Putri Cahyani; Bahari, Bahari; Muhammad Aswar Limi (International journal of technology and education research, 2024)
This study aims to determine the profitability and feasibility of sago-based product ventures in the Bagea Sukses Bersama household industry located in East Kolaka Regency. The research was conducted in Simbune Village, Tirawuta Subdistrict, East Kolaka Regency, Southeast Sulawesi Province, in May 2024. The object of this study is the Bagea Sukses Bersama household industry, which produces various types of sago-based products, including bagea and other sago biscuit products derived from agricultural sago. The focus of the research is on the business owner and the workers directly involved in the industry. The data analysis methods used include profitability analysis and Revenue and Cost Ratio (R/C ratio) analysis. The results of the study show that 1) The profit earned by the Bagea Sukses Bersama household industry amounts to Rp4,800,200 per month. This profit reflects the amount or nominal value gained by Bagea Sukses Bersama, influencing the profitability and feasibility of the business, and 2) The total revenue generated is Rp8,100,000 per month, while the total production cost is Rp3,299,800 per month, resulting in an R/C ratio of 2.45. This ratio indicates that each unit of cost incurred generates revenue 2.45 times greater than the cost, or that every Rp1 invested in production costs yields Rp2.45 in revenue